O ENSINO DA FILOSOFIA NAS DIRETRIZES DE JEAN MAUGÜÉ E NO HISTORICISMO DO PENSAMENTO DE JOÃO DA CRUZ COSTA: PIONEIRISMO NA UNIVERDSIDADE DE SÃO PAULO - Almeida, Vinicius Tadeu de (2015)
This study was developed with the aim of refleting the importance of the Teaching of Philosophy in the Brazilian historical background in accord with the paulistana´s conjectural. We have pointed through the Decree nro. 6.283 of January 25th, 1934, in which was established as the first Brazilian University (Universidade de São Paulo) in the words of Vita “pioneering initiative in Brazil” (1969, p.16). Inspired in the traditional academic model of the French philosophical culture, Faculdade de Filosofia, Ciências e Letras assumed since their contiguous methodologies up to the intellectual procedures, by favoring the development of the interdisciplinarity of the cultural formation. A confluence set by intense ideological involvements structured from the modern progress, infusing scientific competences in the professional faculty incorporated into the University, just as well train teachers in the secondary education (SCHWARTZMAN, 2006, p.163). Thus, the School of Philosophy would be the propulsive nucleus. Yet, the centralized teaching of Philosophy´s thinking model assigns as an intellectual technical superiority and accumulated knowledge, hardly distinguishes from the educational competence conquered in other countries, by the potential formation of the Philosophy teachers Jean Maugüé (1955,1982) and João da Cruz Costa (1945,1960,1961,1967). Mauguë points out that the Philosophy formation is directly assigned to the teacher and the student, in which its dedicate themselves. In the writing of Ensino de Filosofia e Diretrizes, he also presents the notion of teaching: the intellectual teacher, involved in a (re) construction of epistemological meanings, legitimized for a pedagogical practice between the well-known and the get to know, in other words, between the taught and the teach. In this regard, it is remarkable that the arguments of the teacher and the philosopher are interlinked, to an extent to be confused and potencialized during the formation. Thus, Cruz Costa, also works when assumes the professorship, yet enhances that the educational process acquires meaning through the História das Ideias as a construction of a philosophical thinking and, therefore the teaching happens when there is a conscience of a historical concentricity, ideas that give meaning coupled with the erudition techniques, that was informed to his students to the changes that passed in our earth, the foreign philosophical trends, and, mostly, for the curious meaning that they have presented in our history (VITA, 1950, p.22). The historical knowledge is the pathway to be done, needed for the humans, that is, the conciliation between the theoretical knowledge and the historical conditions.